2020
DOI: 10.1371/journal.pone.0229236
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in health-related quality of life in people with severe mental illness

Abstract: Introduction and purpose The purpose was to analyze socioeconomic and clinical factors of psychosocial functioning and self-perception in relation to health-related quality of life (HRQOL) in people with severe mental health illness (SMI) by gender. Materials and method A cross-sectional study was conducted on a sample of 133 women and 90 men. Recorded variables: HRQOL, SF-36 Physical Component Scores (PCS) and Mental Component Scores (MCS); sociodemographic and clinical data on psychosocial and self-perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Broadening the picture, gender-specific differences have been emphasized for conceptualizations of patients' presenting difficulties, treatment plans, and mental and medical healthcare pathways [34][35][36][37]. Overall, available evidence suggests that women tend to report higher HRQoL impairments in the context of psychological [38][39][40] or medical difficulties [41,42]. For chronic tinnitus, similar patterns emerged with women describing higher levels of emotional tension, psychological distress, and functional impairment [43][44][45][46], although these findings remain inconclusive [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…Broadening the picture, gender-specific differences have been emphasized for conceptualizations of patients' presenting difficulties, treatment plans, and mental and medical healthcare pathways [34][35][36][37]. Overall, available evidence suggests that women tend to report higher HRQoL impairments in the context of psychological [38][39][40] or medical difficulties [41,42]. For chronic tinnitus, similar patterns emerged with women describing higher levels of emotional tension, psychological distress, and functional impairment [43][44][45][46], although these findings remain inconclusive [47,48].…”
Section: Introductionmentioning
confidence: 99%
“…No gender differences appeared on any of the investigated variables, which is noteworthy as some research shows, for example, that women with mental illness rate their quality of life at a lower level than men do [ 51 ]. Although no study reporting worse quality of life for men could be found, there is also research that indicates an absence of gender differences [ 42 ].…”
Section: Discussionmentioning
confidence: 88%
“…In the current study, the QoL domains affected by MBDs were not related to gender, although they were associated with increased age. A Spanish study that evaluated the QoL of people with severe mental illness identified that women’s overall mean QoL in the physical component was significantly lower than that of men, and that the factors associated with QoL also differed by gender 33 .…”
Section: Discussionmentioning
confidence: 99%